Hexagon Fraud Theory in Detecting Financial Statement Fraud in Infrastructure Sector Companies - Segalani, Panca Dian; Hasnawati, Hasnawati (Syntax Corporation Indonesia, 2024)
The fraud hexagon theory states that financial statement fraud is influenced by several factors. This research aims to test empirically and see the influence of pressure, opportunity, rationalization, capability, arrogance and collusion on financial statement fraud using modified jones model as the dependent variable. The analytical method used in this research is multiple linear regression analysis with purposive sampling technique. The sample in this research numbered 99 consisting of 33 infrastructure sector companies that were listed on the Indonesia Stock Exchange (IDX) and published annual reports for the period 2020 to 2020. 2022. The research results show that the rationalization variable has a positive effect on financial report fraud. However, the variables pressure, opportunity, ability, arrogance and collusion have no effect on financial statement fraud